A Chinese Case of Cornelia de Lange Syndrome Caused by a Pathogenic Variant in SMC3 and a Literature Review - Li, Ran; Tian, Bowen; Liang, Hanting; Chen, Meiping; Yang, Hongbo; Wang, Linjie; Pan, Hui; Zhu, Huijuan (Frontiers in Endocrinology, 2021)
Purpose Cornelia de Lange syndrome (CdLS) is a rare congenital developmental disorder, and cases caused by variants in SMC3 are infrequent. This article describes a case of CdLS related to a pathogenic variant in SMC3 and performs a literature review. Methods We collected clinical data and biological samples from a 12-year-old boy with “short stature for 11 years”. Gene variants in the proband were detected by whole-exome sequencing, and the variants in his parents were verified by Sanger sequencing. All SMC3-related CdLS patients from the PubMed and Web of Science databases were collected and summarized using the available data. Results A pathogenic variant in SMC3 in the proband, c.1942A>G, was identified. Neither of his parents carried the same variant. Twenty-eight patients were diagnosed with CdLS with variants in SMC3, including the cases in this study and those reported in the literature, where half of the variant types were missense, followed by 32% (9/28) with a deletion and 11% (3/28) with a duplication. All patients showed symptoms of verbal development delay and intellectual disability to different degrees, and 90% patients had long eyelashes while 89% patients had arched eyebrows. Conclusion This study summarized different gene variants in SMC3 and the frequencies of the various clinical manifestations according to the reported literature. For CdLS caused by SMC3 variants, short stature and facial dysmorphic features are the two most important clinical clues. Definite diagnosis of this rare disease may be challenging clinically; thus, it is significant to use molecular diagnosis.